Tension-Compression Fatigue Induced Stress Concentrations in Woven Composite Laminate - Eldho Mathew (MDPI AG, 2021)
Tension-compression (T-C) fatigue response is one of the important design criteria for carbon-fibre-reinforced polymer (CFRP) material, as well as stress concentration. Hence, the objective of the current study is to investigate and quantify the stress concentration in CFRP dog-bone specimens due to T-C quasi-static and fatigue loadings (with anti-buckling fixtures). Dog-bone specimens with a [(0/90),(45/−45)4]s layup were fabricated using woven CFRP prepregs and their low-cycle fatigue behaviour was studied at two stress ratios (−0.1 & −0.5) and two frequencies (3 Hz & 5 Hz). During testing, strain gauges were mounted at the centre and edge regions of the dog-bone specimens to obtain accurate, real-time strain measurements. The corresponding stresses were calculated using Young’s moduli. The stress concentration at the specimen edges, due to quasi-static tension, was significant compared to quasi-static compression loads. Furthermore, the stress concentration increased with the quasi-static loading within the elastic limit. Similarly, the stress concentration at the specimen edges, due to tensile fatigue loads, was more significant and consistent than due to compressive fatigue loads. Finally, the effects of the stress ratio and loading frequency on the stress concentration were noted to be negligible.